2015
DOI: 10.1002/chem.201500594
|View full text |Cite
|
Sign up to set email alerts
|

From the N‐Heterocyclic Carbene‐Catalyzed Conjugate Addition of Alcohols to the Controlled Polymerization of (Meth)acrylates

Abstract: Among various N-heterocyclic carbenes (NHCs) tested, only 1,3-bis(tert-butyl)imidazol-2-ylidene (NHC(tBu) ) proved to selectively promote the catalytic conjugate addition of alcohols onto (meth)acrylate substrates. This rather rare example of NHC-catalyzed 1,4-addition of alcohols was investigated as a simple means to trigger the polymerization of both methyl methacrylate and methyl acrylate (MMA and MA, respectively). Well-defined α-alkoxy poly(methyl (meth)acrylate) (PM(M)A) chains, the molar masses of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
(74 reference statements)
1
29
0
Order By: Relevance
“…This desirable feature successfully suppresses premature crosslinking of the product. Similarly, it was recently demonstrated that MMA can be oligomerized in a more controlled manner in the presence of alcohols or hydroxyl‐functionalized polyether using 5‐tBu in DMF at 25 °C . Finally, it was also shown that dimethylacrylate (DMA) can be converted to unsaturated polyester (Scheme ) by application of TPT at 80 °C in toluene in the presence of aromatic alcohols (radical scavengers) .…”
Section: Polymerization Of Acrylic Monomersmentioning
confidence: 94%
“…This desirable feature successfully suppresses premature crosslinking of the product. Similarly, it was recently demonstrated that MMA can be oligomerized in a more controlled manner in the presence of alcohols or hydroxyl‐functionalized polyether using 5‐tBu in DMF at 25 °C . Finally, it was also shown that dimethylacrylate (DMA) can be converted to unsaturated polyester (Scheme ) by application of TPT at 80 °C in toluene in the presence of aromatic alcohols (radical scavengers) .…”
Section: Polymerization Of Acrylic Monomersmentioning
confidence: 94%
“…The nickel N-heterocyclic carbene complexes have also been used in the polymerization of methylmethacrylate [315] (Scheme 58). The complexes (173), (175), (178), (180), (208), (220) and (261) were effective catalysts for the polymerization of methylmethacrylate [84].…”
Section: Methylmethacrylate Polymerizationmentioning
confidence: 99%
“…Organopolymerization [42][43][44][45] has become an important method of polymer synthesis, especially when metal-free products or processes are of main interest. For example, since the pioneering work of Hedrick and Waymouth et al [46][47][48], N-heterocyclic carbene (NHC) mediated polymerization [49][50][51][52] has advanced considerably to cover now not only the ringopening polymerization of heterocyclic monomers [53][54][55][56], but also step-growth polymerization [57][58][59], chain-growth addition polymerization of linear (acrylates, methacrylates) [60][61][62] and cyclic acrylic monomers (MMBLs) [63][64][65][66], group-transfer polymerization [67][68][69][70], Lewis pair polymerization [19][20][21][71][72][73][74][75][76] and proton-transfer polymerization [77,78]. We have recently reported the organocatalytic and chemoselective polymerization of multivinyl-functionalized γbutyrolactones, including VMBL, γ-vinyl-β-methyl-α-methylene-γ-butyrolactone and DAMBL, with NHCs [66].…”
Section: Introductionmentioning
confidence: 99%